Non-phagocytic Activation of NOX2 is Implicated in Progressive Non-alcoholic Steatohepatitis During Aging - Jiang, Joy X. (Hepatology, 2020)
Older patients with obesity/type II DM frequently present with advanced non-alcoholic steatohepatitis (NASH). Whether this is due to specific molecular pathways that accelerate fibrosis during aging, is unknown. Activation of the Src homology 2 domain containing collagen-related (Shc) proteins and redox stress have been recognized in aging, however their link to NASH has not been explored. Shc expression increased in livers of older patients with NASH, as assessed by RTqPCR or western blots. Fibrosis, Shc expression, markers of senescence and NADPH oxidases (NOXs) were studied in young/old mice on fast food diet (FFD). To inhibit Shc in old mice LV-shShc vs. control-LV were used during FFD. For hepatocyte-specific effects, fl/fl Shc mice on FFD were injected with AAV8-TBG-Cre vs. control. Fibrosis was accelerated in older mice on FFD, and Shc inhibition by LV in older mice, or hepatocyte-specific deletion resulted in significantly improved inflammation, reduction in senescence markers in older mice, lipid peroxidation and fibrosis. To study NOX2 activation, the interaction of p47(phox) (NOX2 regulatory subunit) and p52Shc was evaluated by proximity ligation, and co-IPs. Palmitate induced p52Shc binding to p47(phox) activating the NOX2 complex, more so at older age. Kinetics of binding were assessed in SH2 or PTB deletion mutants by biolayer interferometry, revealing the role of SH2 and the PTB domains. Lastly, an in silico model of p52Shc/p47(phox) interaction using RosettaDock was generated. CONCLUSION: Accelerated fibrosis in the aged is modulated by p52Shc/NOX2. We show a novel pathway for direct activation of the phagocytic NOX2 in hepatocytes by p52Shc binding and activating the p47(phox) subunit that results in redox stress, and accelerated fibrosis in the aged.